Effect of Polyherbal Teat Dip Solution on Somatic Cell Count, Standard Plate Count and Prevention of Bovine Sub-Clinical Mastitis - Datta, Manisha; sarma, kalyan; Prasad, Hridayat; Dutta, Tapan; Eregowda, Chethan Gollahalli; Rajesh, Justus Babykutty; Kalita, Girin (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Mastitis is the most common and costly disease affecting dairy cattle worldwide. The long-term use of antimicrobial drugs in farm management poses serious health risks to humans. For pre-milking teat dipping, various teat cleaning disinfectants are currently used. Therefore, to find out its safer natural alternatives, different plant materials like leaves of Ocimum sanctum, Azadirachta indica, Aloe barbadensis and rhizome of Curcuma longa were collected to develop a polyherbal teat dip solution and to observe ABST against E. coli, S. aureus and Streptococcus spp., which were isolated from mastitic milk. The aqueous extract of these herbs showed antibacterial activity against all above pathogens in different concentrations (from 100 mg/mL to 700 mg/mL). According to the result of ABST of selected plant material, a polyherbal teat dip solution was prepared and used on 125 lactating cows divided into three groups, the control group (Gr-1, n=25), Gr-2 (polyherbal teat dip application, n=50) and Gr-3 (commercial teat dip application-Amoxicillin, n=50). The somatic cell count (SCC) and standard Plate count (SPC) were estimated on day 0, 15 and 30 post-applications. The SCC and SPC of milk showed a significant (p<0.01) decrease from day 0 to day 15 and 30 after the application of Gr-2 product and there was no significant difference between Gr-2 and Gr-3 on day 15 and 30. The application of polyherbal teat dips solution before and after milking decreased SCC and SPC with similar efficacy to commercial teat dip solution. Therefore, it can be concluded that polyherbal teat dip solution may be used as an alternative for the prevention of bovine mastitis.